Potential of using microalgae to sequester carbon dioxide and processing to bioproducts - Balan, Venkatesh; Pierson, James; Husain, Hasan; Kumar, Sandeep; Saffron, Christopher; Kumar, Vinod (Royal Society of Chemistry, 2023)
Algae are microscopic photosynthetic prokaryotic or eukaryotic organisms that can naturally grow in fresh or marine water in the presence of sunlight. Algae are capable of sequestering CO2 and utilize nutrients like nitrates, phosphates, and other micronutrients in water to increase their body mass. In the past few decades, algal biomass has been investigated by the scientific community because of its promising applications in producing renewable food, feed, fuels, and chemicals. Additionally, microalgae's ability to fix large amounts of greenhouse gas (GHG) such as carbon dioxide (CO2) has led researchers to investigate microalgae as an alternative way of combating climate change by sequestering flue gas containing CO2 emitted from industries such as coal power plants, cement, steel, and petroleum refineries. This review outlines different sources of CO2 emissions and capturing technology including microalgae. Details about the methods of cultivating and separating the algal biomass followed by thermochemical and biochemical conversion to fuels/chemicals, microalgae-derived bioplastics, and microalgae biomass blended plastic are outlined in this review. Commercially viable continuous and semi-continuous biorefining processes such as hydrothermal flash hydrolysis and environmental benefits of using microalgae as carbon sinks and wastewater treatment are also provided.